The Influence Of Moving Teacher Management In Improving The Quality Of Learning In State Primary Schools Of Bireuen District - Syukratun Nufus; Bahrun Bahrun; Khairuddin Khairuddin (STKIP Singkawang, 2024)
One of the policies of the independent learning program is that teachers can be innovative in implementing learning, position themselves as leaders who are sensitive to students' learning situations and conditions and become independent learning leaders. Driving teacher management aims to improve the quality of learning through developing teachers' pedagogical, personality, social and professional competencies. The aim of this research is toknow about the Management of Driving Teachers in Improving the Quality of Learning in Bireuen Regency Public Elementary Schools. This research uses an experimental approach with research design One Group Pretest-Posttest Design. Data collection techniques use observation, interviews and tests. The data analysis technique carried out in this research uses qualitative and quantitative data analysis. The results of this research show that: (1) The stages in driving teacher management consist of: planning, driving teachers, participating in coordinating in preparing the school's vision and mission according to the demands of the independent curriculum and developing the latest learning strategies, implementing driving teachers in improving the quality of learning, namely inviting other fellow teachers. to design learning based on students' needs so that they are able to determine appropriate learning styles, and driving teacher evaluation in improving the quality of learning, namely preparing evaluation instruments, carrying out initial, middle and final (as, of & for) assessments of learning to determine students' progress in a material and carry out reflection as a follow-up to improve further learning; 2) The results of the t test show a significant score of 0.02, which shows that there is an influence of driving teacher management on the quality of elementary school learning in Bireun Regency with an increase of around 40%.